2003
DOI: 10.1002/smi.956
|View full text |Cite
|
Sign up to set email alerts
|

Coping with post‐traumatic stress symptoms following relationship dissolution

Abstract: The aim of this paper is to investigate the relationship between post-traumatic stress symptoms resulting from relationship dissolution and coping style. The hypothesis was that some degree of post-traumatic stress symptoms would be evident among the sample and that the coping strategies of seeking social support, escape-avoidance, self-controlling and accepting responsibility would be associated with such symptoms. Eighty-eight university students who had experienced the dissolution of a romantic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…The standard deviation for the Ways of Coping Checklist domains scores varied in the literature with different patients population (62)(63)(64). The sample size calculation is based on the hypothesis that head and neck cancer patients with low levels of anxiety or depression use different coping skills compared to those with high levels of anxiety or depression 6-12 months following the diagnosis of their cancer.…”
Section: Sample Sizementioning
confidence: 99%
“…The standard deviation for the Ways of Coping Checklist domains scores varied in the literature with different patients population (62)(63)(64). The sample size calculation is based on the hypothesis that head and neck cancer patients with low levels of anxiety or depression use different coping skills compared to those with high levels of anxiety or depression 6-12 months following the diagnosis of their cancer.…”
Section: Sample Sizementioning
confidence: 99%
“…At a basic level, the social and psychological transition to singledom requires adjustment to a new, or at least altered, identity (Amato, 2000), which is most obviously threatening for one's sense of continuity. Relationship dissolution has been associated with emotional experiences such as hurt, frustration, grief and depression (Chung et al, 2003). There is some evidence that in the immediate aftermath of relationship dissolution individuals may experience depressive symptoms, which can either gradually wane or develop into full-blown depression (Park et al, 2011;Rhoades et al, 2011).…”
Section: Relationship Dissolutionmentioning
confidence: 99%
“…In the context of heterosexual couples, it has been noted that the dissolution of a romantic relationship can often be experienced as a highly stressful and sometimes psychologically traumatic event (Chung et al, 2003). At a basic level, the social and psychological transition to singledom requires adjustment to a new, or at least altered, identity (Amato, 2000), which is most obviously threatening for one's sense of continuity.…”
Section: Relationship Dissolutionmentioning
confidence: 99%
“…Chung et al (2003) found that after relationship breakups, participants displayed as much avoidance as a clinical comparison sample. Additionally, Lepore and Greenberg (2002) found that avoidance strategies after breakups were related to short-term increase in upper respiratory symptoms in a control group.…”
Section: Emotional Processing and Copingmentioning
confidence: 94%
“…Rumination and avoidance are symptoms associated with DSM-IV recognized disorders, namely depression, PTSD, and anxiety (Blalock & Joiner, 2000;Nolen-Hoeksema, 1991). Chung et al (2003) demonstrated that participants who had experienced a breakup showed avoidance at significantly higher levels than medical students, historically a stressed sample.…”
Section: Hypothesis Imentioning
confidence: 99%